2015
DOI: 10.1002/path.4550
|View full text |Cite
|
Sign up to set email alerts
|

Molecular profiling of tumour budding implicates TGFβ‐mediated epithelial–mesenchymal transition as a therapeutic target in oral squamous cell carcinoma

Abstract: Although tumour budding is an adverse prognostic factor for many cancer types, the molecular mechanisms governing this phenomenon are incompletely understood. Therefore, understanding the molecular basis of tumour budding may provide new therapeutic and diagnostic options. We employ digital image analysis to demonstrate that the number of tumour buds in cytokeratin-stained sections correlates with patients having lymph node metastases at diagnosis. The tumour bud count was also a predictor of overall survival,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
136
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(147 citation statements)
references
References 54 publications
9
136
0
2
Order By: Relevance
“…Prrx1 regulates the differentiation of mesenchymal precursors and plays a central role in pancreatic regeneration and carcinogenesis 31. More importantly, Prrx1 promotes metastasis through the induction of the EMT in hepatocellular carcinoma and breast cancer 32. Here, Prrx1 was identified as an important downstream target of miR‐655.…”
Section: Discussionmentioning
confidence: 99%
“…Prrx1 regulates the differentiation of mesenchymal precursors and plays a central role in pancreatic regeneration and carcinogenesis 31. More importantly, Prrx1 promotes metastasis through the induction of the EMT in hepatocellular carcinoma and breast cancer 32. Here, Prrx1 was identified as an important downstream target of miR‐655.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, the tumor microenvironment is in fact increasingly complex and mediates the signaling crosstalk of different tumor cell and stromal cell types and tumor regions 1214,32 . Previous proteomic studies of oral cancer have used LDM to evaluate tumor cells of epithelial origin 29,3335 and Jensen et al 17 analyzed the ITF and the central area of the OSCC tumor; however, they did not evaluate the stroma from each region.…”
Section: Discussionmentioning
confidence: 99%
“…Grading systems based on the ITF 4,16 have demonstrated reliable predictive value for OSCC prognosis, thus highlighting the importance of this area for molecular profiling and for the identification of potential biomarkers, as it is considered a key region in the dynamic progression of malignant tumors 12,13,17 . The presence of neoplastic islands, classified as large or small according to the number of cells in the ITF, has been described as the most aggressive pattern compared to tumors with a more uniform growth pattern, as tumor invasion occurs in a more widespread manner as cellular islands or single cells 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Almangush et al reported the combination of tumor budding (B) and a tumor depth (D) as a BD model for the prognostication of early oral tongue carcinoma [17]. The correlation between tumor budding and epithelial-mesenchymal transition has also been suggested [14,18,19]. As tumor budding was thought to be a microscopic indicator of tumor invasiveness, we focused on this feature for predicting late lymph node metastasis in this study.…”
Section: Introductionmentioning
confidence: 94%